Jim & me eaudiobook - Gutman, Dan (Baseball Card Adventure, 2009)
Prolific young adult author Dan Gutman has hit home runs with many boys thanks to his spectacular baseball fan time-traveling tales-including Babe Me and Honus Me. Jim Me finds Stosh and his nemesis Bobby Fuller joining forces to help one of their heroes. Native American baseball legend Jim Thorpe was an Olympic champion-but then lost his medals due to scandal. Now only Stosh and Bobby have the power to change history and give Jim the legacy he deserved.